Macroeconomic policy and climate change: Some developing countries' perspectives - Ferdinand Bakoup (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
Among the factors that determine countries' macroeconomic performance and outlook, climate change has, since the 1990s, progressively gained significant prominence in national and global public policy discussions, and consequently also in macroeconomic policy analysis. This paper discusses the role of climate change in macroeconomic analysis and argues that a complete macroeconomic analysis of climate change requires that three complementary questions be asked, and adequate answers provided. The first question relates to the macroeconomic impacts of climate change or put differently, the impact of climate change on macroeconomic performance and policy. The second question relates to the impacts of macroeconomic policies on climate change. The third and most important question relates to ways of assessing the macroeconomic performance of climate change policies. While the first and second questions have often been addressed in the still nascent literature on the macroeconomics of climate change, attention to the third question is still at a very early stage of development. This paper, therefore, focuses on the third question and suggests some issues to consider in addressing it, especially in developing countries' context. In this perspective, the paper suggests that moving from the preparation of NDCs to the preparation of "Just NDCs" is a critical first step towards strengthening the macroeconomic performance of climate change policies. This should be informed by a definition of the macroeconomic stability properties of "just" climate change policies. Mobilizing adequate international financing for climate action will be an important determinant of the macroeconomic performance of climate change policies in developing countries. Developing countries should prioritize strengthening their capacities in these areas.
Keywords: 330; Developing countries; Climate change; Macroeconomics